2008
DOI: 10.4049/jimmunol.180.6.3782
|View full text |Cite
|
Sign up to set email alerts
|

Human Lymphocyte Activation Gene-3 Molecules Expressed by Activated T Cells Deliver Costimulation Signal for Dendritic Cell Activation

Abstract: Data have been reported on the in vivo adjuvant role of soluble lymphocyte activation gene-3 (LAG-3) recombinant protein in mouse models and on its ability to support the in vitro generation of human, tumor-specific CTLs. In this study, we show that soluble human rLAG-3 protein (hLAG-3Ig) used in vitro as a single maturation agent induces phenotypic maturation of monocyte-derived dendritic cells and promoted the production of chemokines and TNF-α inflammatory cytokine. When given in association with optimal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…There was however a marked increase in the expression of LAG3 by KO Treg. Although LAG3 negatively regulates T cell function, in its soluble form it can have stimulatory properties on dendritic cells [18]. Thus over-expression of LAG3 by KO Treg may activate APC to enhance, rather than suppress, expansion of CD4+ T cells in the lymphopenic environment.…”
Section: Resultsmentioning
confidence: 99%
“…There was however a marked increase in the expression of LAG3 by KO Treg. Although LAG3 negatively regulates T cell function, in its soluble form it can have stimulatory properties on dendritic cells [18]. Thus over-expression of LAG3 by KO Treg may activate APC to enhance, rather than suppress, expansion of CD4+ T cells in the lymphopenic environment.…”
Section: Resultsmentioning
confidence: 99%
“…Further, this same group showed that antibodies to LAG-3 could inhibit the suppressive function of Treg cells. In contrast to studies in mice, in humans soluble LAG-3 protein can promote a TH1 immune responses, a response that is generally appreciated to be therapeutic in a majority of tumor models (44). Additional investigations will be required to determine the role for LAG-3 in generating DC that are suppressive or promote the development of a therapeutic immune response.…”
Section: Introductionmentioning
confidence: 95%
“…LAG‐3 is poorly expressed on peripheral lymphocytes, but can be expressed on recently activated T cells . In addition to inhibiting T‐cell function, binding of MHCII by LAG‐3 initiates APC maturation pathways and promotes IL‐12 and TNF‐α production . LAG‐3 expression at the genital mucosa could, therefore, play a role in antigen processing and innate immunity to sexually transmitted infections and normal flora by modulating immune activation at the FGT.…”
Section: Introductionmentioning
confidence: 99%